ANALISIS KOMPARATIF EFEKTIVITAS DAN EFISIENSI PENGENDALIAN BIAYA LINGKUNGAN DALAM MEWUJUDKAN ECO-EFFICIENCY PERUSAHAAN PERTAMBANGAN (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2022)
Mining companies are required to show greater environmental care and responsibility. Environmental cost classification and reporting can help achieve the effectiveness and efficiency of environmental cost control. This study aims to determine and compare the effectiveness and efficiency of environmental cost control of mining companies, determine the company's eco-efficiency, and determine its effect on eco-efficiency. This comparative descriptive research and quantitative research uses secondary data, namely data on environmental costs and financial data of PT TIMAH Tbk. (TIMAH) and PT Aneka Tambang Tbk. (ANTAM) for 2016-2020 which collected through documentation. Data were analyzed using ratio analysis, trend, and simple linear regression. The results of the study found that: (1) TIMAH and ANTAM have not adopted environmental cost reporting based on the theory of Hansen et al., (2) Environmental cost control ANTAM more effective than TIMAH, (3) Environmental cost control TIMAH more efficient than ANTAM, (4) The highest eco-efficiency of TIMAH obtained in 2016, while the highest eco-efficiency of ANTAM obtained in 2018, (5) The effectiveness of environmental cost control has a significant effect on eco-efficiency. However, the efficiency of controlling environmental costs has no significant effect on eco-efficiency. Keywords: Effectiveness and Efficiency, Environmental Cost, Eco-efficiency